COST CONCEPTS FOR CONTROL. - Anthony, Robert N. (The Accounting Review, 1957)
In this article the author discusses the cost concept for control process. He explains the background of deliberations that led to the adoption of the framework. He mentions the examination of various types of cost constructions used for control purposes and the contents of control process. He explains the three groups of control concepts which are, communication of information about approved plans, motivation of people and the reporting of performance. Explaining the concept of communication, he mentions that approved budget is the end result of a planning process and a communication device which tells each unit of an organization about what the management expects it to do during the budget period. He illustrates costs as a motivating device with an example and the possibilities and implications involved in each possibility of the concept. He mentions briefly the points which focus on the limitations of cost as a motivating device. He explains cost as a basis for reporting and appraising as a paradox with concepts relevant to the area.